Interaction Model in Reducing the Prevalence of Stunting for Poor Citizens in Subang Regency - Hirawan, Zaenal; Akhmad, Dede; Peirisal, Tepi; Sugiyono, Sugiyono; Purnama, Dody Wahyudi; Digyo, Digyo; Suherlan, Suherlan (Universitas Padjadjaran, 2025)
Stunting prevalence reduction regularly becomes a strategic issue in development, not only in the regional context, but also nationally and even globally. It requires the government to initiate an intersectoral policy. The research aimed to explain the cross-cutting model programme, which was conducted by regional agents of the Subang Regency Government and governance elements, which combined with poverty reduction. Research used qualitative design which primary data was obtained from key actors of the Subang Regency Stunting Prevalence Reduction Acceleration Team. Data was processed to design a power and interest mapping, then a convergence model of regional agency and nongovernment organization. For secondary data, it was implemented to determine regional priority on policy implementation. Research results indicated that, based on the power and interest aspect, from 21 participants' observation, there were 3 regional agencies that occupied the players position, 4 regional agencies on the contest setter position, 12 regional agencies and several nongovernment agencies on the subject position, and 2 regional agencies occupied the crowd position. Practically, these participants applied convergency steps based on specific intervention, sensitive intervention, technical support, and administrative support. These steps implemented by using priority on sub-district region that had high percentage on poverty